OXYGEN ISOTOPE GEOCHEMISTRY OF THE AMPHIBOLES: ISOTOPE EFFECTS OF CATION SUBSTITUTIONS IN MINERALS - STRATEGIES FOR HIGH PRECISION AND ACCURACY WITH LASER HEATING - Kohn M.J.; Valley J.W. (My University, 1998)
The occurrence of coexisting amphiboles in rocks and the likelihood of concurrent isotope closure allows equilibrium oxygen isotope fractionations among the amphiboles to be recovered from natural samples. Oxygen isotope analyses of mineral separates using laser fluorination show that coexisting amphiboles increasingly partition 18O in the order: hornblende # gedrite < cummingtonite =< anthophyllite. The observed fractionations at ~575°C are: Δ(Ged-Hbl) = 0.8%%, Δ(Cum-Hbl) = 0.9, Δ(Cum-Ged) = 0.2, Δ(Ath-Ged) = 0.3, and Δ(Ath-Hbl) > 0.9. Previously published data for hornblende, actinolite, glaucophane, and garnet show that Δ(Act-Hbl) ~ 0.2, Δ(Gln-Grt) # 1, and Δ(Hbl-Grt) ~ 0. Thus, glaucophane strongly partitions 18O relative to the calcic amphiboles. The fractionation between two amphiboles of arbitrary composition can be predicted from the known fractionations for mica endmembers, pyroxene endmembers, and exchange components such as CaAl(NaSi)-1, NaAl(CaMg)-1, CaMg-1, MgFe-1, FeMn-1, KNa-1, KAl( Si)-1, and Fe3+Al-1. Applications of the exchange component method reproduce measured amphibole fractionations to within +/-0.1 to +/-0.2%%, whereas other predictive methods cause misfit for typical metamorphic hornblende of =<0.5%% at 575°C. Although the isotope effects of cation exchanges may be small at high-T, they magnify dramatically for minerals formed in surficial, diagenetic, and low-T metamorphic environments. Different composition clays are predicted to have equilibrium δ18O differences of 2-9%%. If the isotope fractionation can be determined for one mineral endmember, then calibrated exchanges allow accurate prediction of the isotope fractionations for intermediate compositions of most ortho-, ring-, chain-, and sheet-silicates.